Transcription factor WRKY46 modulates the development of Arabidopsis lateral roots in osmotic/salt stress conditions via regulation of ABA signaling and auxin homeostasis. (18th September 2015) - Ding, Zhong Jie; Yan, Jing Ying; Li, Chun Xiao; Li, Gui Xin; Wu, Yun Rong; Zheng, Shao Jian
Summary The development of lateral roots (LR) is known to be severely inhibited by salt or osmotic stress. However, the molecular mechanisms underlying LR development in osmotic/salt stress conditions are poorly understood. Here we show that the gene encoding the WRKY transcription factor WRKY46 (WRKY46) is expressed throughout lateral root primordia (LRP) during early LR development and that expression is subsequently restricted to the stele of the mature LR. In osmotic/salt stress conditions, lack of WRKY46 (in loss‐of‐function wrky46 mutants) significantly reduces, while overexpression of WRKY46 enhances, LR development. We also show that exogenous auxin largely restores LR development in wrky46 mutants, and that the auxin transport inhibitor 2, 3, 5‐triiodobenzoic acid (TIBA) inhibits LR development in both wild‐type (WT; Col‐0) and in a line overexpressing WRKY46 (OV46). Subsequent analysis of abscisic acid (ABA)‐related mutants indicated that WRKY46 expression is down‐regulated by ABA signaling, and up‐regulated by an ABA‐independent signal induced by osmotic/salt stress. Next, we show that expression of the DR5:GUS auxin response reporter is reduced in roots of wrky46 mutants, and that both wrky46 mutants and OV46 display altered root levels of free indole‐3‐acetic acid (IAA) and IAA conjugates. Subsequent RT‐qPCR and ChIP‐qPCR experiments indicated that WRKY46 directly regulates the expression of ABI4 and of genes regulating auxin conjugation. Finally, analysis of wrky46 abi4 double mutant plants confirms that ABI4 acts downstream of WRKY46. In summary, our results demonstrate that WRKY46 contributes to the feedforward inhibition of osmotic/salt stress‐dependent LR inhibition via regulation of ABA signaling and auxin homeostasis.